2014
DOI: 10.4067/s0717-73482014000300006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación de los músculos respiratorios en la parálisis diafragmática bilateral

Abstract: Assessment of respiratory muscle strength in bilateral diaphragmatic paralysis Measurement of respiratory muscle strength is useful in order to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Supinkski et al concluded that, in response to phrenic nerve stimulation (PdiTw), Pdi predicts extubation duration better than maximum inspiratory pressure (Pimax), which also anticipates successful extubation with a value of -30 cmH PdiTw estimates respiratory muscle strength, evaluating electromyographic signals and conduction velocity in each hemidiaphragm; its range of normality is 8.8-33 cm H 2 O, but, having such a wide range, it would only be useful to identify severe muscle weakness [42]. It requires highly trained personnel because of its harmful results in terms of pain caused by electrical cervical stimulation, as it can overestimate muscular strength [42], as well as because it can be difficult to locate the phrenic nerve [38,43].…”
Section: Measurement Of Transdiaphragmatic Pressurementioning
confidence: 99%
See 2 more Smart Citations
“…Supinkski et al concluded that, in response to phrenic nerve stimulation (PdiTw), Pdi predicts extubation duration better than maximum inspiratory pressure (Pimax), which also anticipates successful extubation with a value of -30 cmH PdiTw estimates respiratory muscle strength, evaluating electromyographic signals and conduction velocity in each hemidiaphragm; its range of normality is 8.8-33 cm H 2 O, but, having such a wide range, it would only be useful to identify severe muscle weakness [42]. It requires highly trained personnel because of its harmful results in terms of pain caused by electrical cervical stimulation, as it can overestimate muscular strength [42], as well as because it can be difficult to locate the phrenic nerve [38,43].…”
Section: Measurement Of Transdiaphragmatic Pressurementioning
confidence: 99%
“…It is avoided to use it without additional tests due to the effort of using it alone [32] Transdiaphragmatic pressure Allows to understand the injuries, the patient-ventilator interaction, VW failure and muscle work in MV [39] It requires highly trained personnel It's difficult to locate the phrenic nerve [42] Esophageal pressure (Pes)…”
Section: Variety Of Devices Not Necessarily Extra Materialsmentioning
confidence: 99%
See 1 more Smart Citation